Artistic paintings and drawings as a source for the ancient urban reconstruction of living towns: the cases of Panormus and Regium Lepidi - Paolo Storchi (Groma)
Artistic paintings and drawings as a source for reconstructing the ancient urban environments of present-day towns: the cases of Panormo and Regium Lepidi. The reconstruction of the ancient appearance of present-day cities is particularly complicated. In this project, to understand ancient Panormo (Palermo) and Regium Lepidi (Reggio Emilia), all available sources have been utilised, an approach that can be applied to every living city in Italy or elsewhere. Drawings, views and engravings of either particular monuments or entire cities are particularly important sources for the reconstruction of ancient towns; they let us see a city much closer to the Roman one than that of today. In this paper we analyse the case studies of the ancient theatre of Palermo and of the amphitheatre of Reggio Emilia.